2022
DOI: 10.3389/fimmu.2022.887256
|View full text |Cite
|
Sign up to set email alerts
|

Elevated IL-19 Serum Levels in Patients With Pernicious Anemia and Autoimmune Gastritis

Abstract: Pernicious anemia (PA) is a megaloblastic anemia consisting of hematological, gastric and immunological alterations. The immunopathogenesis of PA is sustained by both autoantibodies (e.g. intrinsic factor (IFA) antibodies and anti parietal cell (PCA) antibodies and autoreactive T cells specific for IFA and the parietal cell proton pump ATPase. Iron deficient anemia (IDA) is a microcytic anemia and represents the most common cause of anemia worldwide. Our work aimed to investigate serum levels of several interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Gastric specimens from eight AIG patients (having no other autoimmune disease) and four HCs were used as source of LPMCs. Specifically, LPMCs were isolated by the dithiothreitol- ethylenediaminetetraacetic acid (DTT-EDTA)-collagenase sequence ( 18 , 19 ). To investigate the proliferative response to gastric H + /K + -ATPase, purified as reported ( 12 ), LPMCs were labeled with carboxyfluorescein succinimidyl ester (CFSE) (CellTrace CFSE dye, Invitrogen, USA) following manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Gastric specimens from eight AIG patients (having no other autoimmune disease) and four HCs were used as source of LPMCs. Specifically, LPMCs were isolated by the dithiothreitol- ethylenediaminetetraacetic acid (DTT-EDTA)-collagenase sequence ( 18 , 19 ). To investigate the proliferative response to gastric H + /K + -ATPase, purified as reported ( 12 ), LPMCs were labeled with carboxyfluorescein succinimidyl ester (CFSE) (CellTrace CFSE dye, Invitrogen, USA) following manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…A study on the cytokine profile of patients with pernicious anemia demonstrated a notable elevation in their serum IL-19 levels compared with healthy controls [19]. Furthermore, an in vitro investigation of gastric lamina propria mononuclear cells derived from patients with pernicious anemia revealed their capacity to produce augmented levels of IL-19.…”
Section: Lymphocytes and Cytokinesmentioning
confidence: 99%
“…However, there are no clues on the pathogenic process mediated by Helicobacter pylori specific T helper 17 lymphocytes in human gastric intestinal metaplasia and gastric dysplasia. Inflammatory mediators (such as cytokines) which in situ originate in the stomach may diffuse into the blood and then be detected [ 38 ]. Serum cytokine levels of gastric premalignant patients somehow mirror the inflammatory milieu , which is ongoing in the gastric mucosa, suggesting that measurement of serum IL-17A might be useful for monitoring the mucosa inflammation of Helicobacter pylori -infected individuals.…”
Section: Introductionmentioning
confidence: 99%